Complementary medicine in the SUS: integrative practices in the perspective of medical Anthropology - Andrade, João Tadeu de; Costa, Liduina Farias Almeida da (Saúde e Sociedade, 2010)
The article examines the contribution of Complementary Medicine to Sistema Único de Saúde (SUS - Brazil's National Health System) in a new institutionalization context. The reflection analyzes official policies of health institutions such as the WHO and the Ministry of Health, in addition to the specialized literature on the subject. The integrative and complementary practices within the SUS, in the midst of a path of increasing legitimacy, value non-biomedical resources and methods related to the health/disease/cure process, enrich diagnostic/therapeutic strategies, and may encourage medical pluralism in Brazil. Thus, the current public health system transports into its interior other traditional knowledge and rationalities, which start to coexist with the logic and conventional services of biomedicine. The article stresses the anthropological discussion about integrality in public health policies, with emphasis on the social, symbolic, and cultural aspects that the sanitary realities necessarily shelter. In conclusion, attention is drawn to the need to investigate the integrality concept, as well as to face the practical challenges its implantation requires.